From reception of classics to outreach: classical reception and American response to war. A case study. Part II - Lauriola, Rosanna (Acta Scientiarum. Language and Culture, 2014)
After providing a theoretical framework pertaining to the field of Reception of Classic in the first part of this essay (LAURIOLA, 2014) and after discussing some related issues from a pedagogical viewpoint, I introduced, as case study, works and initiatives by a psychiatrist (SHAY, 1991, 1994, 2002), an American director (DOERRIES, 2008), and two scholars (MEINECK, 2010a, b, 2012; TRITLE, 1998, 2000, 2010) who have been proposing a use of Classical Literature as a therapeutic and awareness-raising tool in response to the problems that modern wars have been causing. Veterans and their family, as well as the whole civic community, are the addressees of their work. What follows is a detailed analysis of those works with the intention both to determine whether they can be classified as work of reception – which, so far, has never been proposed – and to discuss the plausibility of this kind of reception, which also turns into social outreach, and how it can be proposed without risking to completely dismiss changes that have occurred in the vision of war, although we may agree that the sufferings of war did not change too much1. Like in the first part, the discussion will be also carried on within a pedagogical discourse. A personal note based on a personal experience will conclude the analysis.